Design of Active Suspension using Robust PID Controller - Mohd Nordin, Mohammad Farhan (Universiti Teknologi PETRONAS, 2010)
This report discusses the final analysis and basic understanding of the chosen topic, which is Design of Active Suspension Using Robust PID Controller. The objective of this research is to propose another method in designing an active suspensien by using robust PID centreller and to analyze the effectiveness ef this method compared to other. This report is divided into a few main seetiens for clarity and easier reference. There are Introduction, Literature Review, Methodology and Result and Discussion. The Introduction part will helps the reader to have a general view on what is Robust PID Controller and how to implement it into an active suspension, in this part; it i~ !!!~ i!lc!~c;ll:l thl:l b!ICkgrol!!\d $ldy, prg\>!em lltlltl:lml:l!!t, gbj~tivl:l gf st\ldy !l!!d also scope of study that being done by the writer. The body of this report will further explain all the literature review and research that being done before regarding the same field of interest, this will include the research done by the writer on the vibration control of vehicle suspension system that have the same interest with the topic discussed in this report. The methodology part will explain on how the sequence will take place in order to complete this project within one year duration. Result and discussion shall discuss on the mathematical modeling based on two type of vehicle model that being proposed for this project. It is also included in this part the programming and simulation done in the MATLAB on how the system goes in passive suspension and also the active suspension based on two aspects which are suspension travel vs time and body mass displacement vs time. Then the validation is dane by comparing the result gain from the analysis with the literature.